Banking structure - Biacora, Estelito C. (Animo Repository, 1997)
The Philippine banking system is composed of the central bank, commercial banks, thrift banks, specialist government banks and rural banks, it is still dominated, though, by the commercial banks, which control about 84% of total resources. Banks ae classified by their capitalisation, and the products and services offered to clients.